TEKNIK PEMBUATAN BUKU AJAR MEMBACA KRITIS DAN KREATIF BERBASIS ARCS (ATTENTION, RELEVANCE, CONVIDENCE, SATISFACTION) UNTUK MAHASISWA PENDIDIKAN BAHASA DAN SASTRA INDONESIA - Iis Suwartini; Ariesty Fujiastuti (BAHASTRA, 2017)
Textbooks that support learning Creative Critical Reading courses are still very minimal. It certainly affects the ability of students to understand reading skills. Students have limited ability to understand the theory due to the limitations of reverence. One effort that can be done is to develop textbooks. Textbooks should be able to motivate students. One effort that can be done is by developing ARCS-based teaching book (Attention, Relevance, Convidence, Satisfaction). This article aims to comply with ARCS-based teaching-learning techniques. Creation of Creative Critical Reading books with ARCS contains four components: awakening and attention to students' attention during learning (Attention), using subject matter that is relevant to the student's life (Relevance), instilling confidence, and cultivating a sense of satisfaction on students to learning (Satisfaction). The expected result in this research is the creation of ARCS-based critical and creative reading book (Attention, Relevance, Convidence, Satisfaction) for Indonesian Language and Literature Education Study Program students.